Neonatal innate immunity response in invasive candidiasis - J. A. G. Suárez; R. J. N. Calumby; D. P. Silva; V. T. Barbosa; F. C. A. Maranhão; I. F. Moreira; M. S. C. Melhem; R. T. F. Moreira (Brazilian Journal of Biology, 2024)
Abstract Infections caused by Candida spp. are frequent in critically hospitalized patients, especially among premature neonates, representing one of the most common healthcare-related infections. Although there is considerable production of current knowledge about the mechanisms of immune response, aspects involved in the newborn's innate defense are not fully understood. The aim of this study was to describe the innate immune mechanisms involved in the defense of neonates against invasive candidiasis. This is an integrative literature review from the Scopus, Scifinder, Medline, Web of Science databases and the electronic libraries ScienceDirect and Scielo, in the period between 2002 and 2020, with rescue based on primary descriptor Immunity Innate plus secondary descriptors Candidiasis Invasive AND Infant Newborn. We have observed the involvement of various mechanisms in the neonatal response against invasive candidiasis, including the recognition, signaling, recruitment, and initiation of an effective immune response. These mechanisms encompass the presence of antimicrobial peptides, phagocytosis, synthesis of reactive oxygen species, inflammatory mediators, and complex cell signaling systems mediated by Pattern Recognition Receptors (PRRs). With this study, it is expected to contribute to the expansion of knowledge about the immunological mechanisms involved in the innate immune response of the newborn against disseminated infections caused by Candida species, and in the same sense, highlight the importance of this knowledge as a reflex in the decrease in mortality in the neonatal period.